2008
DOI: 10.1016/j.ultsonch.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bleaching by ultrasound on fatty acids and minor compounds of olive oil. Qualitative and quantitative analysis of volatile compounds (by SPME coupled to GC/MS)

Abstract: The effects of bleaching using high power ultrasound (20 kHz) on the quality of olive oil were considered in this study, in order to verify the modifications that can occur in fatty acid composition and minor compounds. During the treatment of olive oil under ultrasonic waves, a rancid odour has been detected. Treated olive oils show no significant changes in their chemical composition but the presence of some volatile compounds, due to ultrasonic treatment. Some off-flavour compounds (hexanal, hept-2-enal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 14 publications
4
32
0
2
Order By: Relevance
“…Reduction in α‐tocopherols under ultrasonic process was observed by Jahouach‐Rabai et al . (). Different forms of tocopherols have vitamin E activity (α > β > γ > δ‐tocopherol) and antioxidant activity (δ > γ > β > α‐tocopherol).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Reduction in α‐tocopherols under ultrasonic process was observed by Jahouach‐Rabai et al . (). Different forms of tocopherols have vitamin E activity (α > β > γ > δ‐tocopherol) and antioxidant activity (δ > γ > β > α‐tocopherol).…”
Section: Resultsmentioning
confidence: 97%
“…According to Jahouach‐Rabai et al . (), the collapse of bubbles and cavitation occurs when the oil is treated by ultrasound for a period of time longer than 20 min and also, oil changes are only seen in the most severe conditions. In this study, the changes in pigment and oil colour were observed at range 20–30 min.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the burnt off-flavour, octanoic acid could be directly involved in its perception, given that it is characterised by an unpleasant rancid smell and taste (Budavari, O'Neal, Smith, Heckelman, & Kinneary, 1996). The formation of decanoic acid methyl ester could be the result of lipid oxidation, which has been reported to occur during sonication and which results in the degradation of lipoperoxides, leading to the formation of deterioration products such as aldehydes, ketones, esters and short organic acids (Chemat, Grondin, Shum Cheong Sing, & Smadja, 2004;Jahouach-Rabai et al, 2008). Moreover, the production of δ-dodecalactone is most likely due to the thermal degradation of δ-hydroxyacids esterified into triglycerides as reported by Dimick, Walker, and Patton (1969), due to the localised high temperatures reached during sonication (Piyasena et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…When it was more than 5.0 min, the fluorescence intensity decreased markedly to 609.8 a.u. Given that oxidation is the main cause of lipid degradation [46], sonication energy beyond the level needed for algal cell disruption might induce lipid oxidation [29]. These results suggested that long ultrasonic treatment could lead to the degradation of lipids and unfavorably affect the Nile red fluorescence intensity.…”
Section: Optimization Of Ultrasound-assisted Nile Red Methodsmentioning
confidence: 99%